Policy Changes for a Nutrition Education Program in Maine: Issues and Implications - Majka, Alan; Fairman, Janet; Yerxa, Kathryn (Maine Policy Review, 2013)
Food insecurity and preventable chronic disease have profound impacts on quality of life and health care costs in Maine. Many government programs have been developed to address these issues; however, effectiveness has often been limited by restrictive policies and less than optimal coordination. In this paper the authors draw upon their research and experiences in Maine, research conducted by others, and state and national statistics to elucidate some of these programs, including their efficacy, limitations, potential and threats to their sustainability. The authors contend that recent federal rule changes allow for greater impact through implementation of evidence-based strategies at the same time that budget cuts threaten to undermine progress. Short-term savings achieved through budget cuts to anti-hunger and preventive health programs may be outweighed in the long-term by decreased academic performance in children, increased health care costs and disability as a result of chronic diseases such as diabetes.